Cumplimiento de la normativa “establecimientos de salud amigos de la madre y del niño (esamyn)” por el personal de enfermería del Hospital General Guasmo Sur, en el periodo junio-septiembre 2024. - Garofalo Manobanda, Luis Augusto (2024)
Compliance with the ESAMyN regulations is crucial for ensuring quality care in prenatal education and newborn feeding. Evaluating nurses' knowledge of these regulations is essential to identify strengths and weaknesses, thus ensuring practices align with established standards. A survey conducted with 30 nurses revealed a high level of knowledge in key areas such as breastfeeding and birth preparation. However, it also identified deficiencies in critical areas like hand hygiene and recognizing hunger cues, highlighting the need for specific training. The methodology employed was quantitative, using structured surveys and descriptive statistical analysis to objectively assess the level of compliance. The most relevant results indicated that over 80% of the nurses have solid knowledge in prenatal education and newborn feeding. However, significant weaknesses were found in understanding hand hygiene and disease prevention through breastfeeding, as well as confusion in applying certain regulations. In conclusion, although the nurses possess a strong foundation in key areas, it is imperative to address the identified weaknesses through continuous training and improvement programs. This will ensure that nursing staff correctly apply the ESAMyN regulations, thereby guaranteeing adequate care in line with established standards.